Haloacetylated Enol Ethers: a Way Out for the Regioselective Synthesis of Biologically Active Heterocycles. Issue 28 (29th July 2021) - Mittersteiner, Mateus; Bonacorso, Helio G.; Martins, Marcos A. P.; Zanatta, Nilo
Abstract: This review describes advances in the synthesis of heterocyclic scaffolds (associated with their biological activity), using haloacetylated enol ethers as precursors. The wide variety of heterocycles that can be prepared using these precursors, together with the high regioselectivity they usually provide, in [3+2] and [3+3] cyclocondensation reactions, make these starting materials powerful tools. The biological evaluation is also highlighted, given that several analogues of commercially available drugs can be easily accessed. Abstract : Haloacetylated enol ethers are suitable starting materials for the regioselective synthesis of biologically relevant heterocyclic scaffolds. With this in mind, this review brings together advances in both synthetic and biological/pharmacological activities.